Mechanical properties and microstructure of ultra-retarded solidification mine tailings waste-based shotcrete - Huazhe Jiao; Qi Wang; Aixiang Wu; Xiaohui Liu; Tingyin He; Hui Wang; Xiaolin Yang; Junqiang Xu; Gongcheng Li; Mingyang Li; Hongdong Shen (Case Studies in Construction Materials)
This study addresses the challenges of excessive fluidity and poor bonding performance in ultra-retarded solidification mine tailings waste-based shotcrete. The research investigates the fundamental mechanical properties of this material by optimizing the proportions of mineral powder (A), soil-rock waste (B), and water content (C). Comprehensive analysis was conducted through mechanical property testing, scanning electron microscopy (SEM), and X-ray diffraction (XRD) to elucidate the hydration mechanisms. The results demonstrate that a mineral powder content of 20 % (A1B2C3 to A1B1C1) yields optimal performance, with compressive, splitting tensile, and flexural strengths reaching 138.5 %, 163 %, and 154 % of baseline values, respectively. Maximum compressive strengths of 16.12 MPa, 24.18 MPa, and 32.08 MPa were achieved under specific mix conditions (C1A1B1). Additionally, increasing the content of A and C was found to extend the setting time of the cementitious material. The optimal mix ratio, comprising 20 % A, 25 % B, and 4 % C, exhibited enhanced hydration degree and superior macroscopic performance. Field construction tests confirmed that the material's viscosity, fluidity, and rapid-setting properties meet practical engineering requirements.